2012
DOI: 10.2215/cjn.07640711
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Very-Low-Protein Diet on FGF23 Levels

Abstract: SummaryBackground and objectives High levels of fibroblast growth factor 23 are associated with mortality, CKD progression, and calcification in CKD patients. The aim of this pilot study is to assess whether a very-low-protein diet (0.3 g/kg per day) with a consequent low intake of phosphorus would reduce fibroblast growth factor 23 compared with a low-protein diet (0.6 g/kg per day) in CKD patients not yet on dialysis.Design, setting, participants, & measurements A prospective, randomized, controlled crossove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 51 publications
6
78
0
2
Order By: Relevance
“…13) Although noncontrolled evidence is not unanimous in this regard, the results of a recent large randomized controlled trial (RCT) indicated that a low-phosphorus diet can be used to decrease serum phosphorus andˆbroblast growth factor-23 levels. 14) Another recent RCT showed that the use of this diet combined with the use of phosphate binders proved to be more eŠective than each of these approaches alone. 15) Therefore, a reduction in the intestinal load of phosphorus is important for the prevention and treatment of CKD-mineral.…”
Section: Discussionmentioning
confidence: 99%
“…13) Although noncontrolled evidence is not unanimous in this regard, the results of a recent large randomized controlled trial (RCT) indicated that a low-phosphorus diet can be used to decrease serum phosphorus andˆbroblast growth factor-23 levels. 14) Another recent RCT showed that the use of this diet combined with the use of phosphate binders proved to be more eŠective than each of these approaches alone. 15) Therefore, a reduction in the intestinal load of phosphorus is important for the prevention and treatment of CKD-mineral.…”
Section: Discussionmentioning
confidence: 99%
“…The source of dietary phosphate seems to have quite a profound effect on changes in FGF23, at least in the short-term, with meat-based protein diets yielding higher levels than plant-based protein diets (despite equivalent phosphate content) (90). Dietary phosphate restriction strategies alone have yielded very modest nonsignificant reductions in FGF23 (91)(92)(93)(94), although quite extreme restriction with a very low-protein diet (,400 mg phosphate/d) has been associated with a significant reduction in circulating levels (92). Overall, reductions in FGF23 (102) did report a significant association between cFGF23 and dietary phosphate intake (assessed by food logs) in 1261 individuals enrolled in the Health Professionals follow-up study.…”
Section: Dietary Phosphate Restriction and Oral Phosphate Bindersmentioning
confidence: 99%
“…Blocking dietary phosphate absorption with phosphate binders may decrease FGF23 levels in patients with CKD (9)(10)(11), but the effects of reducing dietary phosphate intake have been less well studied and yielded inconsistent results (12)(13)(14). Additional limitations of the existing literature on FGF23 reduction in CKD include lack of information on the longerterm effectiveness of dietary interventions, sparse data on the efficacy of strategies based on outpatient dietary counseling that are feasible in usual clinical practice, and uncertainty about the effect of combining outpatient dietary counseling with phosphate binders.…”
Section: Introductionmentioning
confidence: 99%